Epileptic spasms are a feature of DEPDC5 mTORopathy. (August 2015) - Carvill, Gemma L.; Crompton, Douglas E.; Regan, Brigid M.; McMahon, Jacinta M.; Saykally, Julia; Zemel, Matthew; Schneider, Amy L.; Dibbens, Leanne; Howell, Katherine B.; Mandelstam, Simone; Leventer, Richard J.; Harvey, A. Simon; et al.
Abstract : Objective: To assess the presence of DEPDC5 mutations in a cohort of patients with epileptic spasms. Methods: We performed DEPDC5 resequencing in 130 patients with spasms, segregation analysis of variants of interest, and detailed clinical assessment of patients with possibly and likely pathogenic variants. Results: We identified 3 patients with variants in DEPDC5 in the cohort of 130 patients with spasms. We also describe 3 additional patients with DEPDC5 alterations and epileptic spasms: 2 from a previously described family and a third ascertained by clinical testing. Overall, we describe 6 patients from 5 families with spasms and DEPDC5 variants; 2 arose de novo and 3 were familial. Two individuals had focal cortical dysplasia. Clinical outcome was highly variable. Conclusions: While recent molecular findings in epileptic spasms emphasize the contribution of de novo mutations, we highlight the relevance of inherited mutations in the setting of a family history of focal epilepsies. We also illustrate the utility of clinical diagnostic testing and detailed phenotypic evaluation in characterizing the constellation of phenotypes associated with DEPDC5 alterations. We expand this phenotypic spectrum to include epileptic spasms, aligning DEPDC5 epilepsies more with the recognized features of other mTORopathies.